Clinical characteristics and 6-month follow-up of adults with and without alcohol use disorder who self-harm - Olsson, Petter; Wiktorsson, Stefan; Strömsten, Lotta M. J.; Salander Renberg, Ellinor; Runeson, Bo; Waern, Margda (Frontiers in Psychiatry, 2024)
Background: Alcohol use disorder (AUD) is associated with suicidal behavior, but prospective clinical studies are lacking. Aim: To compare clinical characteristics and 6-month outcomes in persons with and without AUD who self-harm. Methods: 804 adults (mean age 33, age range 18-95, 541 women and 263 men, 666 with suicide attempts and 138 with non-suicidal self-injuries at index) at three Swedish university hospitals took part in a research interview that included the Mini International Neuropsychiatric Interview (MINI). Subsequent non-fatal suicidal behavior within six months was identified by record review; suicides were identified by national register. Results: At index, 39% of the men and 29% of the women had AUD. Over two thirds of these cases (69%) were identified by the MINI, but not by clinical AUD diagnosis. While trait impulsivity was more common among persons with AUD than those without (56% vs 36%, Padj = <.001), impulsivity in connection with the index attempt was noted in half of the participants in each group (48% vs 52%, Padj = 1). Subsequent suicidal behavior (fatal/non-fatal) occurred in 67 persons with AUD (26%) and in 98 without AUD (18%), a 60% higher risk among persons with AUD (OR = 1.60, 95% [CI 1.13-2.28], P = .009). Four persons with AUD (2%) and six without (1%) died by suicide within 6 months. Conclusion: Almost a third of patients presenting at psychiatric emergency settings after self-harm fulfilled criteria for AUD, but clinicians often missed this diagnosis. Risk for subsequent suicidal behavior was elevated in patients with AUD. Educational interventions to improve recognition of alcohol use disorder may aid clinicians in the assessment and management of patients who present with self-harm.